Debt equity waps and financial development in the Caribbean - Boamah, Daniel ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Discusses the main principles involved in debt swaps, concentrating on their economic implications, and how such implications have influenced specific country programmes. Discusses also the possible application of the principles to regional and national debt issues.